2022
DOI: 10.1371/journal.pgph.0000797
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to substance and current substance among school-going adolescents in Timor-Leste

Abstract: Few studies have examined how exposure to substance influences adolescent’s use of substance in Timor-Leste. We assessed this relationship using nationally representative data from Timor-Leste to address this gap. Data was pulled from the 2015 Timor-Leste Global school-based student health survey. Data of students aged 13-17years (N = 3700) from class 7–11 across schools in Timor-Leste were analyzed for this study. Second-hand smoking exposure (AOR = 1.57 [1.31, 1.89] and parental tobacco use, AOR = 1.94 [1.54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
(73 reference statements)
2
3
0
Order By: Relevance
“…Our final analysis using logistic regression reveals male gender, recent family history of substance use, and family satisfaction as significant predictors of substance use among adolescents. The present study found that male adolescents are four times more likely than female adolescents to use substances, which is consistent with previous studies indicating that males use substances more than females [23,36,37,39,40,51]. Our study shows the likelihood of substance use among adolescents was 2.68 times (CI: 1.11 -6.43) higher among adolescent boys from substance-using families.…”
Section: Multiple Logistic Regression Analysis Of Significant Variablessupporting
confidence: 92%
See 1 more Smart Citation
“…Our final analysis using logistic regression reveals male gender, recent family history of substance use, and family satisfaction as significant predictors of substance use among adolescents. The present study found that male adolescents are four times more likely than female adolescents to use substances, which is consistent with previous studies indicating that males use substances more than females [23,36,37,39,40,51]. Our study shows the likelihood of substance use among adolescents was 2.68 times (CI: 1.11 -6.43) higher among adolescent boys from substance-using families.…”
Section: Multiple Logistic Regression Analysis Of Significant Variablessupporting
confidence: 92%
“…Our findings indicate that 16.8% of adolescents had a family history of recent substance use. This finding was consistent with other studies that identified familial environment as a social element in youth substance use [11,[36][37][38][39]. We based our hypothesis on Albert Bandura's social learning theory and Ajzen's theory of planned behavior.…”
Section: Multiple Logistic Regression Analysis Of Significant Variablessupporting
confidence: 88%
“…The higher rates amongst males in our study are also consistent with other studies. 16 , 30 While this could indicate a need for specific targeting of prevention programs toward males, it still needs to be noted that the prevalence of current use of any form of tobacco product among females is high at 17.9% and ever use even higher at 23.8%. This again points to the need for national regulations and enforcement which will impact on reducing smoking in the overall population—including adults.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, West Africa had the lowest proportion of alcohol use among adolescents at 28.21%. The rise in alcohol use among school-going adolescents is linked to experiences of hunger, bullying, physical fights, material influence and parental substance abuse 2 21 40 41. As a global public health and social problem, the prevention of adolescent alcohol use requires governments in sub-Saharan Africa and other regions of the world to consider scaling up interventions for the prevention and treatment of substance abuse in line with the Sustainable Development Agenda 2030 42.…”
Section: Introductionmentioning
confidence: 99%